The Impact of Socioeconomic Conditions and Residential Areas on the Development of Gross Motor Skills in Elementary School Age Children - Hariadi, Imam; Winarno, Mashuri Eko; Fadhli, Nurrul Riyad; Yudasmara, Dona Sandy; Taufik; Aji, Galih Purnomo (UNIB Press, 2024)
This study analyzed the differences in gross motor skills in children aged 7-9 years in urban and rural areas and the influence of socioeconomic conditions on them. The study involved 100 children evenly divided between the two areas, with measurements using the AMC-2 instrument. The results showed significant differences in gross motor skills between urban (M=138.8) and rural (M=127.9) children with p=0.003. Urban children performed better in locomotor (70.3 vs 65.2) and object control (68.5 vs 62.7). Multiple regression analysis confirmed that both socioeconomic conditions (B=0.45, p=0.004) and residential area (B=0.39, p=0.008) had a significant effect on gross motor skills. These findings indicate the importance of considering environmental and socioeconomic factors in the development of children's gross motor skills.